Pengaruh Tekanan Screw Press Pada Proses Pengepresan Daging Buah Menjadi Crude Palm Oil - T Hasballah; Enzo W.B Siahaan (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2018)
One of the tools used in the pressing system is screw press, which is useful for separating oil from fruit flesh. In this process the fruit enters and is ground by a threaded shaft or worm screw press which carries and suppresses the fruit mass that is put into the press cage. On the other hand there is a hydraulic system in the form of cone-shaped rods at the ends which serve to narrow the entry and exit of fruit masses. This results in the fruit being pressed and pressed so that the oil comes out of the fruit flesh. Due to the large amount of palm oil losses that occur in the pressing process, it can therefore reduce the yield of Crude Palm Oil (CPO) produced. From this explanation it can be concluded that the hydraulic pressure on the screw press unit is very important to note so that the loss of palm oil can be reduced as small as possible where the hydraulic pressure set is equal to 50-60 Bar. As for the maintenance of the equipment, it is necessary to know the amount of pressure that occurs in the press cage, which is caused by the fruit pulp style and the force that occurs in the worm screw press so that a comparison between the hydraulic pressure and the pressure that occurs in the screw press is obtained.